Van der Waals solid phase epitaxy to grow large-area manganese-doped MoSe2 few-layers on SiO2/Si. (7th May 2019) - Vergnaud, Céline; Gay, Maxime; Alvarez, Carlos; Dau, Minh-Tuan; Pierre, François; Jalabert, Denis; Licitra, Christophe; Marty, Alain; Beigné, Cyrille; Grévin, Benjamin; Renault, Olivier; Okuno, Hanako; et al.
Abstract: Large-area growth of continuous transition metal dichalcogenides (TMDCs) layers is a prerequisite to transfer their exceptional electronic and optical properties into practical devices. It still represents an open issue nowadays. Electric and magnetic doping of TMDC layers to develop basic devices such as p-n junctions or diluted magnetic semiconductors for spintronic applications are also an important field of investigation. Here, we have developed two different techniques to grow MoSe2 mono- and multi-layers on SiO2 /Si substrates over large areas. First, we co-deposited Mo and Se atoms on SiO2 /Si by molecular beam epitaxy in the van der Waals regime to obtain continuous MoSe2 monolayers over 1 cm 2 . To grow MoSe2 multilayers, we then used the van der Waals solid phase epitaxy which consists in depositing an amorphous Se/Mo bilayer on top of a co-deposited MoSe2 monolayer which serves as a van der Waals growth template. By annealing, we obtained continuous MoSe2 multilayers over 1 cm 2 . Moreover, by inserting a thin layer of Mn in the stack, we could demonstrate the incorporation of up to 10% of Mn in MoSe2 bilayers.